Riesgos por las tensiones de paso y de contacto con valores subestandares en una subestación eléctrica de 13,8 kv a 0,24/0,12 kv. - Panchana, Jhon Eugenio (2010)
The present work shows the analysis of the risks in passing for the tensions and of contact in the substation Libertad, located in the city of Santa Elena's La Libertad county, in the plant of the National Corporation of Regional Electricity Santa Elena. The areas Technique, Collections, Accounting, Planning, as well as the piazza of 13,8 kV and of the bank of transformers they are part of the present analysis. Firstly one carries out a visual inspection of the areas previously mentioned to identify the factors of risks that can impact in passing in the generation of the tensions and of contact, this with the purpose of carrying out the calculations of the evaluation of risks by means of the Check List. Then with the obtained information you proceeded to carry out the application of the appraisement of risks by means of the appraisement methodology it Fine. Finally with the obtained results to proceed to take the controls and measures to minimize the risks.